A comparison of different heat maintenance methods implemented during a simulated half-time period in professional Rugby Union players. Issue 3 (March 2018) - Russell, Mark; Tucker, Reuben; Cook, Christian J.; Giroud, Thibault; Kilduff, Liam P.
Abstract: Objectives: In thermoneutral conditions, half-time is associated with reductions in body temperature that acutely impair performance. This laboratory-based study compared active, passive, and combined methods of half-time heat maintenance. Design: Randomised, counterbalanced, cross-over. Methods: After a standardised warm-up (WU) and 15 min of rest, professional Rugby Union players ( n = 20) completed a repeated sprint test (RSSA1). Throughout a simulated half-time (temperature: 20.5 ± 0.3 °C; humidity: 53 ± 5%), players then rested (Control) or wore a survival jacket (Passive) for 15 min, or performed a 7 min rewarm-up after either 8 min of rest (Active), or 8 min of wearing a survival jacket (Combined). A second RSSA (RSSA2) followed. Core temperature (Tcore ) and peak power output (PPO; during countermovement jumps; CMJ) were measured at baseline, post-RSSA1, pre-RSSA2. Results: All half-time interventions attenuated reductions in Tcore (0.62 ± 0.28 °C) observed in Control (Passive: −0.23 ± 0.09 °C; Active: −0.17 ± 0.09 °C; Combined: −0.03 ± 0.10 °C, all p < 0.001) but Combined preserved Tcore the most (p < 0.001). All half-time interventions attenuated the 385 ± 137 W reduction in Control PPO (Passive: −213 ± 79 W; Active: −83 ± 72 W; Combined: +10 ± 52 W; all p < 0.001); with best PPO maintenance in Combined (p ≤ 0.001). The fastest sprints occurred in RSSA2 in Combined (6.74 ± 0.21 s; p < 0.001) but Passive (6.82 ± 0.04 s) and Active (6.80 ± 0.05 s) sprints were 0.4% (p = 0.011) and 0.8% (p = 0.002) quicker than Control (6.85 ± 0.04 s), respectively. Conclusions: While the efficacy of passive and active heat maintenance methods was supported throughout a simulated half-time, a combined approach to attenuating heat losses appeared the most beneficial for Tcore and subsequent PPO and sprint performance in professional Rugby Union players.